Effect of a crack on the nonlinear behavior of a stiffened composite panel - Beghdad, Houda; Rahal, Nacer; Souici, Abdelaziz; Zatir, Sara; Benmahdi, Khaled; Aouad, Halima (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: During their lifetime, ships and aircraft are subjected to severe service and aerodynamic loads that can cause structural damage and cracking. These cracks grow and propagate over time. Extending the life of a damaged structure is a very important area of research. In this context, the repair of composite panels is recommended to restore the performance of cracked structures. Methods: In order to minimize the concentration of stresses at the bottom of a crack, to stop and even to delay the propagation of this crack, this study seeks to propose a two-dimensional analysis by the software ANSYS to predict the effect of the propagation of a possible crack on the nonlinear behavior of cracked stiffened composite panels. Results: The results from this analysis will be a very good reference for improving performance and repairing cracked composite panels using stiffeners. Conclusion: It is recommended to provide patches for repairing cracked panels based on the modeling given in this study.